How Does The Sun Make Weather ? - Williams, Judith (New Jersey. Enslow Elementary., 2005)
Does the sun make it rain? Do the seasons change because of the sun? How do you measure temperature? Learn the answers to these questions, and many others, as you start reading about the sun.
Primary
Keywords: 1.Weather.